Differentiation between temporary and real non-clearability of biotinylated IgG antibody by avidin in mice - Dou, Shuping; Virostko, John; Rusckowski, Mary; Greiner, Dale L.; Powers, Alvin C.; Liu, Guozheng (Frontiers in Pharmacology, 2014)
Although an increasing number of antibody conjugates are being used in the clinic, there remain many unmet needs in antibody targeting. Normal tissue background is one of the key issues that limits the therapeutic efficacy and detection sensitivity. Background reduction coupled with dose increase may provide the required target accumulation of the label or toxin at an acceptable normal tissue background. However, the knowledge about the in vivo interaction between antibody and a clearing agent is currently inadequate for designing a rational clearance regimen or system. The current investigation focuses on the clearability of antibody for background reduction, a topic which is of importance to antibody targeting in general. The investigation employs pretargeting as a research tool and avidin as a model clearing agent. By comparing the effects of natural clearance at a longer post-injection time and avidin clearance, we demonstrated that avidin clearance is much more effective. By directly attaching avidin to a biotinylated antibody prior to injection, we found that the biotinylated antibody in blood, once bound to the clearing agent, can be removed from the circulation immediately and completely, while the real non-clearable antibody without biotin stay. The study of multiple avidin injections confirmed that the presence of clearable biotinylated antibodies after an avidin injection is due to their temporary inaccessibility and subsequent return from tissue compartments. The collective clearance efficiency of 91% by three avidin injections indicates a continuous IV infusion would be recommended to remove all of the biotinylated IgG molecules. In conclusion, the use of antibody pretargeting as a tool in this study has improved understanding of the incomplete clearance by avidin and can aid in overcoming this obstacle.